Small and medium food enterprises in Malaysia: institutional support and policy perspectives - Mohamed Arshad, Fatimah; Mohd Noh, Kusairi; Saari, Mohd Yusof (Sage Publications, 2013)
In Malaysia, SMEs constitute 99.2 per cent of the manufacturing establishments while the food SMEs or SMFES account for only about 1 per cent of the total. The SMEs are engine of growth, growing at a rate higher than the country’s average growth rate. However, the SMFEs sector has not progressed in tandem with the increase in demand for food due to rise in population and income. Malaysia has instituted a number of policy innovations to steer its SME development through the National SME Development Council (NSDC), which mobilizes 15 ministries and 60 agencies to support this sector on all aspects—finance, infrastructure, entrepreneurial training, legal support and so on. This article provides a review of the SMFEs in Malaysia and examines the institutional support available for this sector. The article concludes that despite the support provided, the SMFEs are plagued with structural problems that require more than institutional support and that include R&D and innovation, infrastructural development and specific policies to address their unique problems.